Teacher's Strategy at Nurul Hakim Modern Boarding School in Improving Santri's Generic Life Skills - Tamami, Azra; Mardianto, Mardianto (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The focus of this research is to find out the teacher's strategy, inhibiting factors, and supporting factors in improving the generic life skills of Nurul Hakim Modern Islamic Boarding School students. The teacher of Nurul Hakim Modern Islamic Boarding School became the subject of the author's research. This research uses qualitative methodology with a case study approach, with data collection techniques, namely observation, interviews, and documentation. Based on the results of research conducted on teachers of the Nurul Hakim Modern Islamic Boarding School, the author found an effective strategy for improving the generic life skills of students, namely the strategy of reflection-training-examination. Making Modern Nurul Hakim Islamic Boarding School succeeded in creating an educational environment that supports the development of character, skills, and potential of students.